The Gospels for all Christians rethinking Gospel audiences - Bauckham, Richard J. (Grand Rapids, MI Eerdmans)
Includes bibliographical references.
Keywords: Bible. N.T. Gospels -- social scientific criticism; Sociology, Christian -- history -- early church, ca. 30-600.